Muscari muglaensis (Asparagaceae, Scilloideae), a new species from southwestern Anatolia - Eker İsmai̇l; Duman Hayri̇; Yildirim, Hasan (Phytotaxa, 2020)
A new species, Muscari muglaensis Eker, H.Duman & Yıldırım sp. nov. (Asparagaceae) from Turkey, is described and illustrated. It is morphologically similar to M. weissii, M. comosum, M. cycladicum and M. elmasii, but differs mainly by its large bulbs and fruit structure from M. weissii and M. comosum, and long pedicels of fertile flowers and transversely growing raceme in fruit from M. cycladicum and M. elmasii. In this study, a comprehensive description, diagnostic characters, original photographs, detailed illustration, geographical distribution, conservation assessment, identification key, observations, and taxonomic comments on the new species are presented.